Radical hope : letters of love and dissent in dangerous times - De Robertis, Carolina; De Robertis, Carolina; Díaz, Junot, 1968-; Garza, Alicia, 1981-; Robinson, Roxana; See, Lisa; Gomez, Jewelle, 1948-; Kunzru, Hari, 1969-; Adielé, Faith; Foroutan, Parnaz; Livingston, Chip; Kahf, Mohja, 1967-; et al. (Vintage Books, a division of Penguin Random House LLC, 2017)
A collection of letters--to ancestors, to children five generations from now, to strangers in grocery lines, to any and all who feel weary and discouraged--written by award-winning novelists, poets, political thinkers, and activists.